Effectiveness of the entomopathogenic fungus Alternaria murispora and the predatory ladybird Harmonia convergens in controlling Phenacoccus solenopsis (Tinsley) - El Aalaoui, Mohamed; Rammali, Said; Kamal, Fatima Zahra; Calin, Gabriela; Rarinca, Viorica; Hritcu, Luminita Diana; Ciobică, Alin; Sbaghi, Mohamed (Frontiers in Sustainable Food Systems, 2025)
IntroductionPhenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is a major pest that causes significant damage to many crops worldwide, necessitating effective control methods.MethodsThis study evaluated five treatments under screenhouse conditions: untreated control, Harmonia convergens (HC) alone, Alternaria murispora (AM) alone, AM+HC, and imidacloprid (positive control). Conducted over two experiments, the study involved weekly monitoring for 5 weeks to assess P. solenopsis and HC densities and treated plants’ visual quality.Results and discussionIn Experiment 1, AM+HC reduced mealybug densities to 2.0 by week 5, compared to 184.2 in the untreated control. Similarly, in Experiment 2, AM+HC decreased densities to 0.8, while the control had 189.6 mealybugs. Egg counts reflected these trends, with AM+HC showing the lowest counts (1.8 in Experiment 1 and 0.8 in Experiment 2) versus the control’s high counts (282.0 in Experiment 1 and 287.3 in Experiment 2). AM+HC had the highest plant visual quality scores (9.8 in Experiment 1 and 9.9 in Experiment 2), while the control scores were much lower (1.2 and 0.3, respectively). Predator densities peaked at 28.1 for HC alone in Experiment 1 and 32.1 in Experiment 2, with AM+HC reaching 14.7 and 18.2, respectively. Mummy counts were initially higher in AM alone but increased significantly in AM+HC by weeks 3 and 4. Experiment 2 had a higher mean temperature (22.17°C) compared to Experiment 1 (20.78°C), though this did not affect treatment efficacy. In conclusion, AM+HC proved most effective in reducing P. solenopsis densities and maintaining plant health, demonstrating its potential as a sustainable alternative to chemical pesticides.